Bribery in Sub-Saharan Africa: The Mediating Effects of Institutional Development and Trust. (February 2019) - Joslyn, Jacqueline
The issue of bribery raises questions about the implications of institutional development and trust in the raw material industry. This paper uses theories of institutionalism and trust to explore path dependence arguments seeking to explain the resource curse puzzle. Institutional development and trust are examined as potential mediators linking mineral extraction/processing to bribery in sub-Saharan African countries. The model suggests potential factors linking raw material industries to institutional development and institutional development to the degradation of interpersonal and generalized trust. The proposed model is tested with data on a sample of sub-Saharan African countries using multilevel logistic regression with promising results.